Pengaruh pengetahuan dan kesadaran pajak terhadap kepatuhan pajak dengan sanksi pajak sebagai variabel moderasi - Pramatatya, R. Aditya Putra; Srimindarti, Ceacilia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to analyze the influence of tax knowledge and taxpayer awareness of taxpayer compliance with tax sanctions as a moderating variable. This study uses primary data in the form of questionnaires to individual taxpayers registered in the Tax Office (KPP) Pratama Semarang Selatan. Sampling technique using an accidental sampling method. Data analysis techniques used are multiple linear regression. The results showed that: 1). Knowledge of Taxation has a positive and significant effect on taxpayer compliance, 2). Taxpayer awareness has a positive and significant effect on taxpayer compliance, 3). Tax sanctions are able to moderate the influence of tax knowledge on taxpayer compliance, 4). Tax sanctions are able to moderate the influence of taxpayer awareness on taxpayer compliance.